Z Przewodnikiem po metafizyce - Biłat, Andrzej (Filozofia Nauki, 2012)
The paper is a review of the book Przewodnik po metafizyce (ed. S. Ko³odziejczyk, WAM, Kraków 2011). The book consists of fourteen essays concerning key issues of metaphysics, mostly written by leading Polish experts. The review contains a number of critical and polemic comments on some of the essays.